Insurgency and Counter-Insurgency in Turkey The New PKK - Plakoudas, Spyridon (Springer International Publishing, 2018)
For readers of Strategy and IR and researchers on the Middle East, the intermittent war between the PKK and Turkey (1984-present) forms the ideal case study as every possible outcome (military victory, peace negotiations and stalemate) and aspect (terrorism, insurgency and civil unrest) of ethnic civil wars have manifested over the years. This monograph offers an up-to-date analysis of an irregular conflict (2004-2017) which spilled over to neighbouring states since 2011 and continues to shape the Middle East through the lens of Strategic Studies. Spyridon Plakoudas is Assistant Professor in Strategy and IR at the American University in the Emirates and Vice President of the think tank KEDISA. .